2013
DOI: 10.1007/s00128-013-0998-3
|View full text |Cite
|
Sign up to set email alerts
|

Outline of Occupational Chromium Poisoning in China

Abstract: The present study analyzed the feature of occupational chromium poisoning in China since the 1980s. The collected data were acquired from 18 previous surveys of chromium poisoning in 14 cities of China. The method of risk assessment was applied to calculate the relative risk and 95% CI, p < 0.05 was considered as a significant risk. The results showed that nasal disease was the most common sign of occupational chromium poisoning, and the prevalence rate of nasal disease was 17.83% in total population of 6,998.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 16 publications
1
21
0
1
Order By: Relevance
“…The high metal levels in human blood have been reported in several previous investigations, which might be attributed to the occupational exposure source (Gil et al 2011;Hodnett et al 2012;Ivanenko et al 2012;Caciari et al 2012;Feki-Tounsi et al 2013a and2013b;Khlifi et al 2013;Khlifi et al 2014a and2014b;Ojo et al 2014;Choi and Kim 2014). Additionally, numerous epidemiological investigations suggested that exposure to toxic metals via occupational exposure has been evermore associated to nasal disease (Yang et al 2013;Sciskalska et al 2014) and sino-nasal cancer (Doll et al 1970;IARC 1990;Barbieri et al 2005;d'Errico et al 2009). …”
Section: Discussionmentioning
confidence: 79%
“…The high metal levels in human blood have been reported in several previous investigations, which might be attributed to the occupational exposure source (Gil et al 2011;Hodnett et al 2012;Ivanenko et al 2012;Caciari et al 2012;Feki-Tounsi et al 2013a and2013b;Khlifi et al 2013;Khlifi et al 2014a and2014b;Ojo et al 2014;Choi and Kim 2014). Additionally, numerous epidemiological investigations suggested that exposure to toxic metals via occupational exposure has been evermore associated to nasal disease (Yang et al 2013;Sciskalska et al 2014) and sino-nasal cancer (Doll et al 1970;IARC 1990;Barbieri et al 2005;d'Errico et al 2009). …”
Section: Discussionmentioning
confidence: 79%
“…Epidemiological data indicate that women working in Cr industries or living in Cr-contaminated environments suffer from several gynecological complications including spontaneous abortion [17,18,90]. Occupational exposure to CrVI during pregnancy decreased intrauterine growth of the fetuses, resulting in low birth weight [91].…”
Section: Discussionmentioning
confidence: 99%
“…Occupational exposure to CrVI is found among approximately one-half million industrial workers in the U.S and several millions worldwide [11,12]. Epidemiological data indicate that women working in Cr industries such as textiles and tanneries have high Cr levels in their blood, urine, umbilical cord and placental tissue [13,14], experience abnormal menses [15,16], spontaneous abortion [17,18], and deliver children with developmental defects [19,20], and low birth weight [21]. …”
Section: Introductionmentioning
confidence: 99%
“…Similar to animal studies, these found: increased spontaneous abortions [37]; decreased intrauterine growth of fetuses resulting in low birth weight [38, 39]; high levels of Cr(VI) in the blood, urine, and umbilical cord blood [38, 40]; and in neonates, Cr(VI) in the cord blood and cord lymphocyte mutations [32, 41]. …”
Section: Introductionmentioning
confidence: 65%